Math, asked by abhishek83307, 1 year ago

factorise the equation by regrouping-
(2x - 3y ) (a - b) + ( 3y - 2x ) (3a - b)​

Answers

Answered by mysticd
1

Answer:

-2a(2x-3y)

Step-by-step explanation:

(2x - 3y)(a - b)+( 3y - 2x )(3a - b)

= (2x-3y)(a-b)-(2x-3y)(3a-b)

= (2x-3y)[(a-b)-(3a-b)]

= (2x-3y)(a-b-3a+b)

= (2x-3y)(-2a)

= -2a(2x-3y)

Therefore,

(2x - 3y)(a - b)+(3y - 2x )(3a - b)

= -2a(2x-3y)

Answered by Anonymous
6

\huge\sf{Answer:-}

(2x - 3y)(a - b) + (3y - 2x)(3a - b) \\  = (2x - 3y)(a - b) - (2x - 3y)(3a - b) \\  = (2x - 3y)(a - b) - (3a - b) \\  = (2x - 3y)(a - b) - (3a + b) \\  = (2x - 3y)( - 2a) \\  =  - 2a(2x - 3y)

So,

 = (2x - 3y)(a - b) + (3y - 2x)(3a - b) \\  =  - 2a(2x - 3y)

Similar questions